2016
DOI: 10.7150/thno.16358
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Negative Surface Charges of Cancer Cells by Multifunctional Nanoprobes

Abstract: A set of electrostatically charged, fluorescent, and superparamagnetic nanoprobes was developed for targeting cancer cells without using any molecular biomarkers. The surface electrostatic properties of the established cancer cell lines and primary normal cells were characterized by using these nanoprobes with various electrostatic signs and amplitudes. All twenty two randomly selected cancer cell lines of different organs, but not normal control cells, bound specifically to the positively charged nanoprobes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
270
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 330 publications
(278 citation statements)
references
References 28 publications
7
270
1
Order By: Relevance
“…All tested cancer cells bound exclusively to the positive NPs (Figure 3, previously published [61]). Except for granulocytes, normal cells had no binding to either type of NPs [61,62]. The negative surface charges are highly sensitive to inhibition of glycolysis and are generated as a result of lactate secretion.…”
Section: Recognition Mechanism By Granulocytes Via Surface Chargesupporting
confidence: 57%
See 1 more Smart Citation
“…All tested cancer cells bound exclusively to the positive NPs (Figure 3, previously published [61]). Except for granulocytes, normal cells had no binding to either type of NPs [61,62]. The negative surface charges are highly sensitive to inhibition of glycolysis and are generated as a result of lactate secretion.…”
Section: Recognition Mechanism By Granulocytes Via Surface Chargesupporting
confidence: 57%
“…We designed two nanoprobes (NPs), one with a positively charged surface and the other a negatively charged surface, that may have resolved the aforementioned problems [61]. Both types of NPs carried two additional properties of being able to capture the attached cells by a magnet and of being identifiable by fluorescence.…”
Section: Recognition Mechanism By Granulocytes Via Surface Chargementioning
confidence: 99%
“…Secretion of large amount of lactate anions from cancer cells and exposure of more phospholipids on the surface of breast cancer cells lead to negatively charged surface of cancer cells as compared to fibroblasts; thus, positively charged BSeNPs may have strong affinity for breast cancer cells, causing enhanced anticancer efficacy of BSeNPs. [43][44][45] Thus, CSeNPs (31%) showed comparatively more inhibition in NIH/3T3 cells than BSeNPs (77%) at 100 ”g/mL ( Figure 7B). In case of HEK293, CSeNPs (17%) caused more inhibition than BSeNPs (30%), as shown in Figure 8B.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Thus, formulations with lower TPP concentration and higher concentration of the grafted polymer conjugate have more positively charged surfaces. Reports have shown that the surface of tumor cells is negatively charged [26][27][28]. Interestingly, the optimized endostatin-loaded nanoparticle has an average positive zeta potential value of 7.95 mV (Figure 4) which predisposed it for direct targeting in squamous cell carcinoma, as later presented in this study [29].…”
Section: Confirmation Of the Physicochemical Properties Andmentioning
confidence: 60%
“…It is interesting to note that the doses of endostatin-loaded nanoparticles presented in this study, administered to the KYSE-30 cells to achieve the antiangiogenic drug levels presented in Figure 12, were in the range of 125-1000 g/mL and were not expected to affect cell proliferation. The positively charged surface of the designed nanocargo, as presented in Figure 4(b), could have facilitated direct binding to the negatively charged surface of KYSE-30 cells having a typical tumor cell surface [26]. Similarly, the shielding effect of the nanoparticles' surface by PEG could have modulated the release of endostatin within the nanoparticle matrix thereby increasing its antiangiogenic efficacy on the treated cells.…”
Section: Confirmation Of Cytocompatibility and Antiangiogenicmentioning
confidence: 99%